Association between air pollution and sleep disordered breathing in children. Issue 5 (4th February 2019) - Sánchez, Trinidad; Gozal, David; Smith, Dale L.; Foncea, Catalina; Betancur, Carmen; Brockmann, Pablo E.
Abstract: Background and Objective: Similar to other respiratory diseases, sleep disordered breathing (SDB) may be exacerbated by air contaminants. Air pollution may have an impact on incidence and severity of SDB in children. The aims of this study were to examine potential associations between the exposure to different air pollutants and SDB symptoms in children. Methods: In this cross‐sectional study, parents from first grade children of elementary schools throughout Chile were included. Data about clinical and family‐related SDB risk factors, and the pediatric sleep questionnaire (PSQ) were obtained. Air pollution and meteorological data were obtained from the Chilean online air quality database. Results: A total of 564 children (44.9% males) aged (median) 6 years (5‐9 year) were included. Prevalence of SDB based on PSQ was 17.7%. When examining air pollutants and conditions, only higher humidity ( β  = 0.005, 95%CI 0.001‐0.009, P  = 0.011) was significantly associated with higher PSQ scores after adjusting for demographic and household variables. Higher ozone (O3 ) levels (OR = 1.693, 95%CI 1.409‐2.035, P  < 0.001), higher humidity (OR = 1.161, 95%CI 1.041‐2.035, P  = 0.008) and higher dioxide sulfur (SO2 ) levels (OR = 1.16, 95%CI 1.07‐1.94, P  < 0.001]) were associated with increased odds of wheezing‐related sleep disturbances after adjusting for confounders. Lower temperature was a significant predictor of snoring at least >3 nights/week, following adjustment (OR = 0.865, 95%CI 0.751‐0.997, P  < 0.05). Conclusion: Sleep respiratory symptoms (wheezing and snoring) are significantly associated with air pollutants such as O3 and SO2 . In addition, meteorological conditions such as humidity and low temperatures may be also associated with SDB‐related symptoms.